Spaces of Estrangement in Luiz Ruffato's Eles Eram Muitos Cavalos. - Beal, Sophia (Romance Notes, 2023)
In 2001, Luiz Ruffato published Eles eram muitos cavalos , one of the most celebrated Brazilian novels of the last thirty years. That same year, the renowned geographer Ana Fani Alessandri Carlos—who has dedicated most of her career to studying São Paulo— published the article "São Paulo hoje: as contradições no processo de reprodução do espaço." Ruffato's and Carlos's texts render a moment just prior to widespread access to the internet and social media that transformed spatial practices, communication, activism, and consumption within global cities. I return to Ruffato's novel over two decades after its initial publication to analyze how it—in ways that dovetail with contemporary Brazilian urban geography— envisions the right to the global city, particularly residents' experience of estrangement. Both Ruffato and Carlos capture the ways that the dominance of the capitalist production of space creates estrangement because residents are disconnected from a social fabric, fearful of the street, and less able to create collective urban memories. As Carlos spatially explains the production of estrangement in São Paulo, Ruffato, employing innovative aesthetic solutions, imagines how individuals experience estrangement in the city. The novel, despite its local specification, conveys, more broadly, residents' sensory and emotional experiences of estrangement in global cities.